Efecto acaricida in vitro del aceite esencial de Lantana camara contra Rhipicephalus (boophilus) microplus, en concentraciones de 10 y 15% - Vidal Lopez, Haydee Briggette (2023)
In the present investigation, the acaricidal effect of Lantana camara essential oil was evaluated by in vitro application in concentrations of 10 and 15% against Rhipicephalus (boophilus) microplus. The design considered for the study was a completely randomized experimental design, with a quantitative methodological approach. The population used for the study consisted of 90 adult ticks of the genus Rhipicephalus (boophilus) microplus that were obtained from adult bovines from the Ceibopamba sector of the Malacatos parish of the Loja canton of the Loja province, the same ones that were randomly sampled and they were divided into 3 experimental groups with 10 observational units each one, distributed for the three treatments applied: control group (olive oil), Treatment 1 (10% Lantana camara oil) and Treatment 2 (Lantana camara oil at 15%). The variables were tabulated using the SPSS program using the ANOVA test, in which treatment was considered the main variation factor, to perform an analysis of variance on the study groups that were raised, together with Tukey's test for perform a comparison of means. From the analysis of results, it was possible to determine the 100% mortality of the adult ticks used in the study. It was not possible to show a significant difference between treatments and a p-value of <0.0001 was obtained, which shows us that the results obtained are not statistically significant. In conclusion, it can be stated that the essential oil of Lantana camara has an acaricidal effect. Keywords: Acaricide, cattle, essential oil, mortality, ticks.